Relationship betwen entrepreneurial behavior dimension and entrepreneurial intention amongst first year students in Universiti Malaysia Sabah, Kota Kinabalu - Fong, Yee Shin (2008)
This study aims to find out entrepreneurial behavior dimensions that affect entrepreneurial intention amongst students in Universiti Malaysia Sabah, (UMS) Kota Kinabalu. A survey was conducted among first year students who are compulsory to take US7222 (Fundamental of Entrepreneurship) in Universiti Malaysia Sabah . A total of 201 usable questionnaires were collected for this study. The finding revealed that a significant positive relationship existing between entrepreneurial behavior dimensions and entrepreneurial intention amongst first years students in Kota Kinabalu. The finding confirms that entrepreneurial attitude and social norms have significant positive effect on entrepreneurial intention amongst first year UMS students in Kota Kinabalu. Interestingly, the finding discovers that attitude is the most important dimension as significant to determine entrepreneurial intention. This study also finds that the parents ever been employed has significant relationship between (attitude, social norms and self efficacy)and entrepreneurial intention. It is suggested that the university management need to pay more attentions and to emphasize on these significant underlying entrepreneurial behavior dimensions (attitude and social norms) in order to enhance entrepreneurial intention.